ANALISIS KUALITAS AIR SUMUR DI DESA MANDURO KECAMATAN KABUH KABUPATEN JOMBANG: ANALISIS KUALITAS AIR SUMUR DI DESA MANDURO KECAMATAN KABUH KABUPATEN JOMBANG - SRI SEPTI DYAH PRATIWI; Yushardi Yushardi; Sudarti Sudarti (Journal of Research and Education Chemistry, 2021)
This study aims to determine the water content of the wells of the people of Manduro Village, Kabuh District, Jombang Regency. Another objective is to know the impact of the water content of the well. This type of research is a case study by exploring various in-depth and actual information. Information gathering was carried out from March to April 2021. The methods used were literature review and land observation. The respondents used were 30 people from Manduro Village and 15 dug and drilled wells. Observation results show that the well is polluted by a fairly high lime content, resulting in considerable losses. The well is also polluted by the content of ammonia (NH3), metal iron (Fe) and metal manganese (Mn). The water quality in Menduro Village, in terms of physical water, contains a fishy smell and smell of rust, a cloudy color, and causes a yellow color attached to the bucket or water storage container, bathroom wall. It identifies that the water contains Fe (Iron) which exceeds the quality. Some of the water also smells of ammonia due to the location of the well which is close to the poultry house and also the disposal of industrial waste. Efforts are being made to make water treatment separate from the water content mixed by the mining soil, the unpleasant odor due to industrial waste, while the efforts of the mine owners have not been realized. water away from the earth mine. With the hope that this effort can be one of the solutions to alleviating the problems that occur in the Manduro Village well water